2011
DOI: 10.1007/s00535-011-0373-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of ischemic small bowel disease by measurement of serum intestinal fatty acid-binding protein in patients with acute abdomen: a multicenter, observer-blinded validation study

Abstract: Serum I-FABP measurement is a non-invasive method that is potentially useful for the efficient identification of patients with acute abdomen who are at risk of small bowel ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 27 publications
3
55
0
4
Order By: Relevance
“…Kanda T et al [17] also found that the serum I-FABP level increased in the presence of not only ischemic disease but also other small bowel disease. Hansen et al [18] reported that the blood I-FABP levels rose in patients with small bowel injury associated with extracorporeal circulation and that there was a strong correlation between such small bowel injury and the onset of the systemic inflammatory response syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…Kanda T et al [17] also found that the serum I-FABP level increased in the presence of not only ischemic disease but also other small bowel disease. Hansen et al [18] reported that the blood I-FABP levels rose in patients with small bowel injury associated with extracorporeal circulation and that there was a strong correlation between such small bowel injury and the onset of the systemic inflammatory response syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…Egy patkányokat használó kísérletes modellben munkacsoportunk kimutatta, hogy a szérum I-FABP-szintjének emelkedése jól korrelál a szövettani minták elemzése során talált intestinalis epithelsejt-károsodás mértékével [25]. Néhány humán vizsgálat során sikerült igazolni, hogy a szérum I-FABP-szintje megemelkedik a. mesenterica superior okklúziója esetén [13,24,26,27,28]. Klinikai gyakorlatban történő alkalmazhatóságát limitál-ja, hogy szérum-I-FABP-emelkedésről nemcsak a vé-konybél ischaemiás károsodása kapcsán számoltak be, hanem a bélrendszer mucosáját érintő nonischaemiás megbetegedések kapcsán is [29].…”
Section: Intestinalis Zsírsavkötő Fehérjeunclassified
“…[10] During surgical procedures such as small intestine transplantation, detection of its exact vitality plays a crucial role. Assessment of the graft viability prior to actual transplantation is decisive for the success of the entire procedure.…”
Section: Resultsmentioning
confidence: 99%